Greenland uplift and regional sea level changes from ICESat observations and GIA modelling - SPADA, GIORGIO; G. Ruggieri; L. S. Sorensen; K. Nielsen; D. Melini; F. Colleoni (Geophysical Journal International, 2012)
We study the implications of a recently published mass balance of the Greenland ice sheet (GrIS), derived from repeated surface elevation measurements from NASA’s ice cloud and land elevation satellite (ICESat) for the time period between 2003 and 2008. To characterize the effects of this new, high-resolution GrIS mass balance, we study the time-variations of various geophysical quantities in response to the current mass loss. They include vertical uplift and subsidence, geoid height variations, global patterns of sea level change (or fingerprints), and regional sea level variations along the coasts of Greenland. Long-wavelength uplifts and gravity variations in response to current or past ice thickness variations are obtained solving the sea level equation, which accounts for both the elastic and the viscoelastic components of deformation. To capture the short-wavelength components of vertical uplift in response to current ice mass loss, which is not resolved by satellite gravity observations, we have specifically developed a high-resolution regional elastic rebound (ER) model. The elastic component of vertical uplift is combined with estimates of the viscoelastic displacement fields associated with the process of glacial-isostatic adjustment (GIA), according to a set of published ice chronologies and associated mantle rheological profiles. We compare the sensitivity of global positioning system (GPS) observations along the coasts of Greenland to the ongoing ER and GIA. In notable contrast with past reports, we show that vertical velocities obtained by GPS data from five stations with sufficiently long records and from one tide gauge at the GrIS margins can be reconciled with model predictions based on the ICE-5G deglaciation model and the ER associated with the new ICESat-derived mass balance.